2018
DOI: 10.1155/2018/2593425
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Dispersed Particle-Blood Flow in the Stenosed Coronary Arteries

Abstract: A mathematical model of dispersed bioparticle-blood flow through the stenosed coronary artery under the pulsatile boundary conditions is proposed. Blood is assumed to be an incompressible non-Newtonian fluid and its flow is considered as turbulence described by the Reynolds-averaged Navier-Stokes equations. Bioparticles are assumed to be spherical shape with the same density as blood, and their translation and rotational motions are governed by Newtonian equations. Impact of particle movement on the blood velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Већи СНЗ у ремоделованим артеријама резултује лошијом ендотелизацијом (19). Већи степен стенозе резултира вишим вредностима СНЗ (20).…”
Section: дискусијаunclassified
“…Већи СНЗ у ремоделованим артеријама резултује лошијом ендотелизацијом (19). Већи степен стенозе резултира вишим вредностима СНЗ (20).…”
Section: дискусијаunclassified
“…Cilla et al 24 mathematically studied the atheroma plaque formation and development in coronary arteries by using Navier–Stokes equations and Darcy’s law for fluid dynamics, convection–diffusion–reaction equations for modeling the mass balance in the lumen and intima. Kaewbumrung et al 25 investigated the dispersed particle-blood flow in the stenosed coronary artery. Their results predicted that the higher level of bio-particle motion directly changed with the pressure drop and wall shear stress and the area of coronary artery with higher density of bio-particles also presented the higher wall shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…Thongsri et al [79] used the CFD to simulate airflow and contaminated particle pathlines in various industrial machines at factories to find the best condition in decontaminating particles from manufacturing. Kaewbumrung et al [10] used the CFD to simulate drug particle flow in the blood system. They reported that the quantity of drugs affected both pressure and wall shear stress.…”
Section: Introductionmentioning
confidence: 99%